DISTINCTIVE FEATURES OF PREGNANCY AND PERINATAL OUTCOMES AMONG WOMEN HAVING UTERINE SCAR - Игитова, Марина Борисовна; Пачковская, Ольга Юрьевна; Боровков, Владимир Анатольевич; Волченко, Ирина Сергеевна (Mother and Baby in Kuzbass, 2018)
An analysis of pregnancy course and perinatal outcomes has been performed among 100 women having uterine scar after single cesarean section in the lower uterine segment, comparing to the control group of women having a recurring pregnancy (100 women) and spontaneous delivery in their anamnesis, chosen for the «copy-pair» research method (balancing features: maternal age, pregnancy number and delivery number, peculiarities of somatic diseases, peculiarities of the obstetrical anamnesis). Women having uterine scar have shown the increase in proportion of the placental disfunction with hemodynamic abnormalities (49 % and 17 %; p < 0.0001), pregnancy resulted in premature delivery more often (10 % and 2 %; p = 0.037). Women having uterine scar had newborns with prenatal development delayed 4 times more often comparing to the control group (12 % and 3 %; p = 0.032), there was increase in rate of the newborns having an asphyxia (13 % and 2 %; p = 0.007). 1.5 times increase of perinatal risks rate was determined (RR = 1.54; 95% CI 1.14–2.08; p = 0.0046) for women having uterine scar after cesarean section.